Neurodevelopmental Outcomes of Infants Born at <29 Weeks of Gestation Admitted to Canadian Neonatal Intensive Care Units Based on Location of Birth - Amer, Reem; Moddemann, Diane; Seshia, Mary; Alvaro, Ruben; Synnes, Anne; Lee, Kyong-Soon; Lee, Shoo K.; Shah, Prakesh S.; Harrison, Adele; Synnes, Anne; Ting, Joseph; Cieslak, Zenon; et al. (The Journal of pediatrics, 2018)
To compare mortality and neurodevelopmental outcomes of outborn and inborn preterm infants born at <29 weeks of gestation admitted to Canadian neonatal intensive care units (NICUs). Data were obtained from the Canadian Neonatal Network and Canadian Neonatal Follow-up Network databases for infants born at <29 weeks of gestation admitted to NICUs from April 2009 to September 2011. Rates of death, severe neurodevelopmental impairment (NDI), and overall NDI were compared between outborn and inborn infants at 18-21 months of age, corrected for prematurity. Of 2951 eligible infants, 473 (16%) were outborn. Mean birth weight (940 ± 278 g vs 897 + 237 g), rates of treatment with antenatal steroids (53.9% vs 92.9%), birth weight small for gestational age (5.3% vs 9.4%), and maternal college education (43.7% vs 53.9%) differed between outborn and inborn infants, respectively (all P values <.01). The median Score for Neonatal Acute Physiology-II (P = .01) and Apgar score at 5 minutes (P < .01) were higher in inborn infants. Severe brain injury was more common among outborn infants (25.3% vs 14.7%, P < .01). Outborn infants had higher odds of death or severe NDI (aOR 1.7, 95% CI 1.3-2.2), death or overall NDI (aOR 1.6, 95% CI 1.2-2.2), death (aOR 2.1, 95% CI 1.5-3.0), and cerebral palsy (aOR 1.9, 95% CI 1.1-3.3). The composite outcomes of death or neurodevelopmental impairment were significantly higher in outborn compared with inborn infants admitted to Canadian NICUs. Adverse outcomes were mainly attributed to increased mortality and cerebral palsy in outborn neonates.